Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
x^4 -x ^3 + 6x^2 - x + n x^2-x+5 x^2+1 - x^4-x^3+5x^2 x^2-x+n - x^2-x+n 0
ĐỂ x4 - x3 + 6x2 -x \(⋮x^2-x+5\)
\(\Rightarrow x-5=0\Rightarrow x=5\)
b , ta có : \(3x^3+10x^2-5⋮3x+1\)
\(\Rightarrow3x^3+x^2+9x^2+3x-3x-1-4⋮3x+1\)
\(\Rightarrow x\left(3x+1\right)+3x\left(3x+1\right)-\left(3x+1\right)-4⋮3x+1\)
mà : \(\left(3x+1\right)\left(4x-1\right)⋮3x+1\)
\(\Rightarrow4⋮3x+1\Rightarrow3x+1\inƯ\left(4\right)=\left\{\pm1;\pm2;\pm4\right\}\)
Nếu : 3x + 1 = 1 => x = 0 ( TM )
3x + 1 = -1 => x = -2/3 ( loại )
3x + 1 = 2 => x = 1/3 ( loại )
3x + 1 = -2 => x = -1 ( TM )
3x + 1 = 4 => x = 1 ( TM )
3x + 1 = -1 => x = -5/3 ( loại )
\(\Rightarrow x\in\left\{0;\pm1\right\}\)
a) \(n^2-4n+29=\left(n^2-4n+4\right)+25=\left(n-2\right)^2+25\)
Để \(n^2-4n+29⋮5\Rightarrow\left(n-2\right)^2⋮5\)
Do 5 là số nguyên tố nên \(\left(n-2\right)⋮5\Rightarrow n=2k+5\left(k\in Z\right)\)
b) \(n^2+2n+6=\left(n+4\right)\left(n-2\right)+14\)
Vậy để \(\left(n^2+2n+6\right)⋮\left(n+4\right)\Rightarrow14⋮\left(n+4\right)\)
\(\Rightarrow n+4\inƯ\left(14\right)=\left\{-14;-7;-2;-1;1;2;7;14\right\}\)
\(\Rightarrow n\in\left\{-18;-11;-6;-5;-3;-2;3;10\right\}\)
c) Ta thấy:
\(n^{200}+n^{100}+1=\left(n^4+n^2+1\right)\left(n^{196}-n^{194}+n^{190}-n^{188}+...+n^4-n^2\right)+n^2+2\)
Để \(n^{200}+n^{100}+1⋮\left(n^4+n^2+1\right)\Rightarrow\left(n^2+2\right)⋮\left(n^4+n^2+1\right)\)
\(\Rightarrow\orbr{\begin{cases}n=0\\n=1\end{cases}}\)
Ta có : n2 + n + 1
= n2 + 2n - n - 2 + 3
= n ( n + 2 ) - ( n + 2 ) + 3
= ( n - 1 ) ( n + 2 ) + 3
Vì ( n - 1 ) ( n + 2 )\(⋮\)n + 2 nên 3\(⋮\)n + 2
=> n + 2\(\in\){ \(\pm\)1 ; \(\pm\)3 }
=> n\(\in\){ - 5 ; - 3 ; - 1 ; 1 } ( tm n\(\in\)Z )